Protective effect of isoquercitrin against acute dextran sulfate sodium-induced rat colitis depends on the severity of tissue damage - Cibiček, Norbert; Roubalová, Lenka; Vrba, Jiří; Zatloukalová, Martina; Ehrmann, Jiří; Zapletalová, Jana; Večeřa, Rostislav; Křen, Vladimír; Ulrichová, Jitka (Pharmacol. Reports, 2016)
BACKGROUND: Isoquercitrin (quercetin-3-O-β-d-glucopyranoside) is a flavonoid that exhibited antioxidant and anti-inflammatory activities in a number of in vitro and in vivo studies. Experimental evidence from rodent models of inflammatory bowel disease is, however, lacking. This study was designed to examine whether isoquercitrin effectively and dose-dependently attenuates acute dextran sulfate sodium (DSS)-induced rat colitis. METHODS: Wistar rats were divided into negative control group (exposed to vehicle only), positive control group (DSS-induced colitis plus vehicle), low isoquercitrin group (DSS pretreated with isoquercitrin 1mg/kg/day) and high isoquercitrin group (DSS with isoquercitrin 10mg/kg/day). Isoquercitrin was administered daily for 14days, and during the last 7days rats drank DSS solution. The effect of isoquercitrin on DSS-induced colitis was assessed clinically (e.g. disease activity index), biochemically (tissue myeloperoxidase activity, local cyclooxygenase-2 expression), using histology (standard hematoxylin-eosin-based histomorphometry, immunohistochemical detection of inducible nitric oxide synthase) and hematology (blood count). RESULTS: Isoquercitrin dose-dependently ameliorated whole colon shortening and mitigated DSS-induced expression of cyclooxygenase-2 and inducible nitric oxide synthase in the descending segment of the organ. However, when different parts of colon were assessed histomorphometrically, the results did not globally support the protective role of this flavonoid. Tissue healing trends observable in the descending colon were not apparent in the rectum, where histological damage was most severe. CONCLUSIONS: We surmise that isoquercitrin may be effective in the prevention of acute colitis. Besides being dose-dependent, the potency of orally administered isoquercitrin may depend on the severity of tissue damage and/or on the site of its action.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; quercetin; Rats, Wistar; kolitida; síran dextranu; Dextran Sulfate; Protective Agents; stupeň závažnosti nemoci; Dose-Response Relationship, Drug; Male; Colitis; krysa rodu Rattus; Random Allocation; Quercetin; mužské pohlaví; zvířata; ochranné látky; Severity of Illness Index; Rats; náhodné rozdělení; potkani Wistar